Global Air Quality Inequality over 2000-2020 - Lutz Sager (CESifo GmbH, 2024)
Air pollution generates vast health burdens and economic costs around the world. Pollution exposure varies greatly, both between countries and within them. But the degree of air quality inequality and its' trajectory have not been quantified at a global level. I use economic inequality indices to measure global inequality in exposure to ambient fine particles smaller than 2.5 microns (PM2.5). I find high and rising levels of global air quality inequality. The global PM2.5 Gini Index rose from 0.30 in 2000 to 0.35 in 2020, exceeding levels of income inequality in many countries. Air quality inequality is mostly driven by differences between countries and less so by variation within them, as decomposition analysis shows. A large share of those facing the highest levels of PM2.5 exposure live in only a few countries. Building on the Global Burden of Disease framework, I find that mortality associated with PM2.5 exposure is even more unequal than pollution exposure itself. The findings suggest that the common focus on inequality within countries overlooks an important global dimension of environmental justice.
Keywords: D63; I14; Q53; 330; air pollution; inequality; health; environmental justice